HEAVY METAL ANALYSIS Ni, Cr AND Zn ON SEDIMENT OF MAMUJU DISTRICT USING INDUCTIVELY COUPLED PLASMA OPTICAL EMISSION SPECTROSCOPY (ICP-OES) - Suraedah Suraedah; Maming Maming (Hasanuddin University, 2018)
This study discusses the heavy metals of Ni and Zn in aquatic sediments of Mamuju Regency using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). Sediment samples were taken at four different locations, namely Rimuku River Estuary, Manakara Beach Pier, Muara River Estuary and Mamuju River estuary. The results obtained for Ni metals ranged from 0.0005 - 0.0019 mg / L and Zn metals ranged from 0.0041 - 0.0066 mg / L and still below the threshold of metal quality standards in the sediment or can be said not polluted.